FOMO, Overconfidence, and Influencers: Key Drivers of Cryptocurrency Investment Behavior - Muhammad Akmal At thariq; Mardiana Mardiana (Owner : Riset dan Jurnal Akuntansi, 2026)
This research examines the psychological and social factors that influence how university students in Malang make investment decisions. This research applied a quantitative approach and engaged 251 participants who were chosen through a purposive sampling method in accordance with established selection criteria. The research utilized a purposive sampling technique to determine the data. Furthermore, it applied Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct effects and moderating interactions among the variables. The findings demonstrate that fear of missing out (FOMO) and overconfidence exert a positive and statistically significant influence on investment decisions. Nevertheless, the presence of influencers attenuates the influence of fear of missing out (FOMO) on investment decisions and fails to moderate the relationship between overconfidence and investment decisions. In general, psychological and social factors continue to shape students’ investment decision-making behavior. The research shows the importance of enhancing financial literacy, particularly among students with limited experience in engaging with high-risk instruments such as cryptocurrency. Controlling the level of overconfidence is very important so that decisions are not influenced by emotions but are based on rational analysis. This research advances the literature by incorporating fear of missing out (FOMO), overconfidence, and influencer involvement as explanatory factors in understanding students’ cryptocurrency investment decisions. This research provides additional insight by introducing a practical model that demonstrates the significance of psychological and social elements among university students in the context of investment.